ANALYSIS OF THE PRESENTATION OF THE FINANCIALSTATEMENTS OF FINANCIAL ACCOUNTING STANDARDS BASED ON COOPERATIVE ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (A Case Study On The Cooperative Loan Agreed Prosperous Branch Pemangkat County Sambas) - ., Sabri B1031131085 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
IAI issued Accounting Standards Entities Without Public Accounting (SAK ETAP) that can accommodate the needs of accounting for entities that do not have public accountability. Therefore, this research aims to find out how the preparation and presentation of financial statements Koperasi Simpan Pinjam Sepakat Makmur based on SAK ETAP and constraints in the preparation of the financial statements based on the SAK ETAP. This research method used descriptive qualitative, data collection techniques by observation, interviews, documentary studies, and literature study. The results showed that in the financial statements that are applied by the Koperasi Simpan Pinjam Sepakat Makmur is still not in accordance with the standards of the financial reporting SAK ETAP. Keywords : Koperasi, Financial Statements, SAK ETAP Â